EFFECTIVENESS OF ELECTRONIC TRIALS (E-COURT) IN BANDUNG STATE COURT ASSOCIATED WITH REGULATION OF THE SUPREME COURT OF THE REPUBLIC OF INDONESIA NUMBER 1 OF 2019 - Aksinuddin, Saim (INFOKUM, 2023)
This study aims to find out how the effectiveness of electronic trials (E-Court) at the Bandung District Court is related to Supreme Court Regulation Number 1 of 2019. This research includes a typology of empirical legal research. The research data was collected by collecting documents related to the effectiveness of electronic trials (E-court) at the Bandung District Court, then the data were processed and presented descriptively and analyzed qualitatively. The analysis was carried out using a normative empirical approach. The results of this study indicate that the researcher considers in terms of effectiveness according to effective standards which is the goal of procedural law according to expectations in Law Number 48 of 2009 concerning Judicial Powers, in which case an effective judiciary is a trial that is carried out simply, quickly, and at low cost, the impact of the application of Supreme Court Regulation Number 1 of 2019 concerning Administration of Cases and Trials in Electronic Courts against the enforcement of the provisions of Article 118 HIR is based on PERMA Number 3 of 2018 Regarding the administration of cases in court electronically, it is enhanced by PERMA Number 1 of 2019 concerning Administration of Cases and Trials in Electronic Courts. The Bandung District Court has implemented e-Court well in the case settlement process. The direct impact felt by justice seekers themselves is that through the implementation of e-court itself, it actually makes it easier for justice seekers to access and control the ongoing process while at the same time saving on litigation costs.